Analisis Kurikulum Merdeka dan Platform Untuk Mewujudkan Pendidikan yang Berkualitas - Dwi Rahmiyana Febriana; Merika Setiawati; Luthfiani (CV. ITTC INDONESIA, 2024)
The aim of this research is to provide a description of the conceptual study of the independent teaching curriculum and platform. An interesting learning management process in schools as an embodiment of quality implementation of the independent curriculum and describes the strategies used in managing learning to improve quality, especially in schools. This type of research includes literature study using descriptive methods. The research results show that independent education programs and platforms emphasize a proactive attitude towards progressive and transformational change. This can be seen from the focus on positive learning development which can restore the productivity of teaching and learning activities. Through project-oriented learning, the learning process can be more flexible, proactive and adaptive. Educators have the freedom to apply learning methods that are considered appropriate for students so that the implementation of teaching and learning activities can be more interesting, in-depth and independent. For this reason, the results of research analysis show that the use of independent learning programs and platforms is consistent with the Indonesian state's efforts to achieve these goals.